Effect of Yoga Asanas on Climacteric Symptoms in Middle Age Women - Vijayalakshmi, S.; Gopal, Baiju (International Journal of Psychosocial Rehabilitation, 2020)
Women differ from men in all aspects the reproductive system is more complex that male and not surprising that is it subject to more frequent disturbances. Puberty, menarche, pregnancy, obesity, thyroid, polycystic ovarian syndrome, menopause etc. are gone through by women in life stages. The terms menopause and climacterium are often used interchangeably in the literature (Neugarten&Kraines, 1965). The word menopause and climacteric are used interchangeably. Climacteric also indicates a ‘change of life’ from one of reproduction, which is coming to an end.The term menopause refers to the cessation of the menses, while climacterium includes the involution of the ovaries and the various processes associated with this involution, including menopause.The Indian Menopause Society’s (IMS) 2008 consensus statement contains important statistics about menopausal symptoms and recommendations to improve healthcare for Indian women.Menopause is a normal part of life, just like puberty. The term “menopause” is commonly used to describe any of the changes a woman experiences either just before or after she stops menstruating, marking the end of her reproductive period. The word ‘menopause’ is derived from men and pauses and is a direct description of the physiological event in women where menstruation ceases to occur. Menopause is a part of every woman’s life. It is the stage when the menstrual period permanently stops. This stage usually occurs between the age of 40 to 60 and is associated with hormonal, physical and psychological changes. The schools of Indian Philosophy are divided as: (Astika) orthodox and (Natika) heterodox. The (Astika) orthodox schools recognize the authority of the Vedas while the (Natika) heterodox schools do not. Nyaya, Vaisesika, Samkhya, Yoga, Mimamsa and the Vedanta are the orthodox schools Indian Philosophy. Among these schools of thought, the Samkhya and the Mimamsa are atheistic in nature. Nyaya, Vaisesika, Yoga and Vedanta are theistic in nature. (Sinha, 2006).Ashtanga Yoga, according to Patanjali, is composed of eight different limbs, labeled in the ancient Indian language of Sanskrit (Satchidananda, 1990). The eight steps of Raja Yoga provide systematic instruction to attain inner peace, clarity, self-control and realisation.The eight limbs of Ashtaga Yoga are: Yama, Niyama, Asana, Pranayama, Prathyahara, Dharana, Dhyana and Samadhi.